Effect of Inter-Fragmentary Gap Size on Neovascularization During Bone Healing: A Micro-CT Imaging Study - Zhou, Zhilun; Yan, Yang; Yu, Hao; Yang, Guanzhong; Su, Hao; Zhang, Tao; Fan, Yubo; Zhao, Feng (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: Neovascularization of the fracture site is of great importance for bone healing and could be influenced by local mechanical environment such as fixation stability and inter-fragmentary gap size. This study aims to reconstruct the neovascularization of fracture site and explore the effect of inter-fragmentary gap size on the spatiotemporal structure of vascularity during bone healing. Methods: Osteotomy was performed on 36 Sprague Dawley (SD) rats on the right tibial diaphysis and the fracture was given fixation with two different inter-fragmentary gap sizes. SD rats received fixation with either a small-sized inter-fragmentary gap (FSF1, 1 mm, n = 18) or a large-sized one (FSF3, 3 mm, n = 18). The left hind limbs were treated as the control group (CON). The animals were sacrificed at different time points (2, 4, and 6 weeks postoperatively, n = 6, respectively) for vascular perfusion and micro-CT imaging. Results: (a) At week 2 and 4, FSF1 samples showed significantly higher vessel volume ratio (VV/TV) and vessel surface density (VS/TV) values than both CON and FSF3 samples; there was no significant difference in either VV/TV or VS/TV values between CON and FSF3 samples. (b) At week 6, both FSF1 and FSF3 samples showed significantly higher VV/TV and VS/TV values than CON samples; FSF3 samples had a significantly higher VV/TV value than FSF1 samples. Discussion: Different inter-fragmentary gap sizes greatly affect the timing of angiogenesis at the fracture site. Fixation with a small inter-fragmentary gap (1mm) benefits neovascularization at the early stages during bone healing and reconstruction, while fixation with a large inter-fragmentary gap (3mm) delays the occurrence of angiogenesis to a later phase.